I think you mean
6x2-15x-21
2x2-5x-7
2x2-7x+2x-7
x(2x-7)+1(2x-7)
(x+1)(2x-7)
9xy2 - 24xy + 15x
15(x-3) :)
5x(2x - 3)
The greatest common factor of 12xy2 + 6x is 6x. The greatest common factor of 12 and 6 is 6, and the greatest common factor of xy2 and x is x. If you took 6x out of both factors, the end result would be 2y2+1
x2 + 6x - 2 can not be factored
18x2 + 15x + 2 = (3x + 2)(6x + 1)
To factorize the expression 6x^2 - 15x, we first look for the greatest common factor, which in this case is 3x. We can factor out 3x from both terms, resulting in 3x(2x - 5). Therefore, the factored form of 6x^2 - 15x is 3x(2x - 5).
3(2x - 1)(x - 2)
3x. 15x - 9x = 6x 9x - 6x = 3x 6x - 3x = 3x 3x - 3x = 0
6x - 14 + 15x + 2 =21x - 12or3 (7x - 4)
Add like terms together: 21x-21
9
-15x - 3
-15x + 1
you just add 6x+9x to get 15x then minus 25 from 18 to get -7 thus the answer will be 15x-7
6x-2=x+135x=15x=3
set formula:15x +75 = 6xbring x to left side:15x - 6x + 75 = 09x = - 75x = - 75/9